Exploring the Impact of Transformation to Fully Online Learning During COVID-19 on Malaysian University Students’ Academic Life and Performance - Al-Kumaim, Nabil Hasan; Mohammed, Fathey; Gazem, Nadhmi A.; Fazea, Yousef; Alhazmi, Abdulsalam K.; Dakkak, Omar (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The COVID-19 pandemic has forced many organizations in the world to fully utilize variety of emerging online communication platform technologies. Higher Education Institutions (HEIs) are among these organizations that obliged students and instructors to use different online communication platforms to insure uninterrupted education process. However, the COVID-19 pandemic has generated many considerable challenges for the global higher education community while using such emerging technologies. The purpose of this study is to analyze university student’s perceptions on the challenges and hurdles they face during the Covid-19 pandemic when they use IT platform applications for online learning activities. This research used mixed methods research with main emphasis on qualitative research, supported by literature content analysis techniques. The data set for this study was collected during peak time of pandemic period between 16th of May 2020 to 5th of Jun 2020. Based on the descriptive analysis using SPSS and the analyzed results using NVivo12 for the data that was collected from 486 students from different universities in Malaysia, students disclosed various obstacles they encounter when they use IT platform applications for online learning. These obstacles are summarized as follows: (1) Work and information overload received from instructors through online learning platforms (2) Technical challenges related to students’ lack of affordability for having online learning support facilities (3) Personal health challenges related to stress and anxiety problems.